(untitled) (Research, Society and Development, 2022)
The aim of this research is to analyze which factors influence in the teacher’s practices to the inclusion of Curriculum Greening categories suggested by ACES Network, through a documental analysis of two universities and 21 interviews with the teachers of two agronomy courses. It was observed that the main difficulties are related to bureaucracy’s aspects around the institutional determinations, the institution’s budget restrictions and the accumulation of functions beyond teaching. Therefore, it is highlighted the importance of a teacher’s staff engaged to the graduation of professionals that will contribute to the sustainable rural development.